CIRCULAR ECONOMY START-UPS: AN INNOVATIVE BUSINESS MODEL FOR SUSTAINABLE FASHION AND TEXTILE WASTE REDUCTION - Edi Supardi; Dmitry Ivanov; Ida Rasmussen (Journal of Social Entrepreneurship and Creative Technology, 2025)
The fashion industry is a primary global polluter, characterized by a linear “take-make-dispose” model that generates enormous textile waste. While the Circular Economy (CE) presents a viable sustainable alternative, the specific business models (BMs) for CE start-ups in this sector remain under-researched. Understanding their unique operational strategies, barriers, and success factors is critical for industry-wide transformation.  This study investigates the innovative business models employed by circular economy start-ups in the sustainable fashion industry. It aims to identify and analyze the key strategies these enterprises use to reduce textile waste while balancing environmental impact with commercial viability. A qualitative, multiple case-study methodology was adopted. The research analyzed ten (n=10) prominent circular fashion start-ups across Europe. Data were collected through semi-structured interviews with founders (n=15) and analysis of internal documents (business plans, impact reports), then coded using a framework based on circular business model archetypes. The findings reveal that successful start-ups integrate multiple circular strategies, primarily “resource recovery” (upcycling, recycling) and “slowing the loop” (rental, repair services). Key innovations were identified in value proposition (marketing sustainability as a premium) and value capture (monetizing waste streams). Significant barriers include scaling reverse logistics and overcoming consumer resistance to non-linear consumption patterns. Circular economy start-ups are essential innovators, but their success demands more than novel design. Their business models require systemic innovation in logistics and robust consumer education. This study concludes that a supportive policy ecosystem is essential for these models to scale and effectively challenge the linear fashion paradigm.